Increased Whole Blood Viscosity Is Associated with the Presence of Digital Ulcers in Systemic Sclerosis: Results from a Cross-Sectional Pilot Study. (29th November 2017) - Korsten, Peter; Niewold, Timothy B.; Zeisberg, Michael; Utset, Tammy O.; Cho, Daniel; Zachary, Lawrence S.; Sweiss, Nadera J.; Volkov, Suncica
Abstract : Objective . To investigate the role of whole blood viscosity in digital ulcer (DU) development in patients with diffuse and limited Systemic sclerosis. Methods . A convenience sample of patients with Systemic sclerosis (SSc) was selected from the adult Rheumatology clinic at the University of Chicago. The study group consisted of patients with SSc (with ulcers present, a history of ulcers, and no ulcers); the control group consisted of matched healthy Rheumatology clinic staff. WBV was measured using a scanning capillary viscometer at different shear rates (1–1000 1/s). Results . Whole blood viscosity as measured by a scanning capillary viscometer was increased in patients with SSc compared to healthy controls (p < 0.0001 ). Additionally, patients with present DU had significantly higher whole blood viscosity when compared to patients with a history of DU and patients with no history of DU (p < 0.0001 ). These findings were most pronounced at lower shear rates between 1 and 10 1/s. Conclusion . Whole blood viscosity might be a contributing factor in DU development in patients with SSc. Further studies with larger patient cohorts are required to fully evaluate how increased WBV contributes to the development of DU and whether the currently available treatment options improve the microcirculation by influencing WBV.